Evaluation of Enrichment, Selective and Differential Media in Isolation and Identification of Salmonella Among Children With Diarrhea - A Tabatabaei Bafroei; B Nikmanesh; A Rahimi Forushani; MM Soltan Dalall; N Aghili (Tehran University of Medical Sciences, 2011)
Background and Aim: Salmonellosis is a gastroenteritis caused by different serotypes of Salmonella and is the most common type of food poisoning in the world. The purpose of this research study is to optimize the conventional method for the isolation of Salmonella SPP from the diarrheic specimens of children. Materials and Methods: Stool specimens were obtained from one hundred patients admitted to Childrens Medical Center for diarrhea. The enrichment media were prepared by 3 methods: Rappaport Vassiliadis broth (RV), Tetrathionate broth (TT), and Selenite Cystine broth (SC). Then, for the isolation of Salmonella SPP, the enrichment methods RV and TT were used and incubated at 42° C, and SC at 37° C. After 24 hours of incubation, the enrichment samples were inoculated into the following 6 different media: Hektone Enteric agar (HE), Rambach agar (RA), CHROMagar Salmnella (CHROMagar Salmonella), Brilliant Green agar (BG), Salmonella-Shigella agar (SS), and Xylose-Lysine-Deoxycholate agar (XLD). Results: In total, 13 out of one hundred samples were identified as Salmonella SPP. All of these 13 Salmonella SPP samples (i. e., 100%) were positive on RV broth; the figures were 8 (61.5%) and 3 (23%) on SC and TT broths, respectively. The highest amount of isolation was found by the combination of RV broth and RA agar (100%). The lowest rate, however, was obtained by the combination of TT agar and BG broth (15.4%).Conclusion: The comparison results of 3 enrichment media and 6 selective media showed that the mixture of RV broth and RA agar would be very fine for the isolation of Salmonella SPP.